Hyperoxia for performance and training - Cardinale, D. A.; Ekblom, B. (Journal of Sports Sciences, 2018)
Recent technological developments have made it possible to use hyperoxia as an enhancement aid during training. Athletes wearing a mask can breathe a higher fraction of oxygen from a stationary or portable apparatus while exercising. A large body of evidence indicates that the oxygen transport capacity, lactate metabolism, power output and work tolerance (endurance) are improved when breathing hyperoxia. The physiological mechanisms underlying these performance improvements, although still not fully elucidated, are based on higher oxygen delivery and reduced central fatigue. Although much is known about the acute effects of hyperoxia, the effect of hyperoxic-supplemented endurance training on performance and the mechanisms beneath training adaptations are not very well understood, especially in well-trained endurance athletes. The few studies on the physiological effects of hyperoxia training have been conducted with conflicting results, discussed in this paper. Potential detrimental effects have not yet been shown experimentally and warrant further investigation.